Near-miss Obstetric Events in a Tertiary Care Teaching Hospital in Nepal: An Audit - Gurung, BS; Koju, RB; Dongol, Y (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This study aims to determine the frequency of near-miss obstetric events and analyze its nature such as reasons for near-miss, organ dysfunction associated and critical management required among pregnant women managed over a 3-year period in a Tertiary Care Teaching Hospital in Nepal. Methods: This hospital based prospective, descriptive study was done from August 2011 to February 2015. Case eligibility was defined by WHO Near-Miss Guidelines. Medical records of the patients and the interview with the patient, accompanying family members and health workers from referral centres were used to generate the data which were filled in the pre-designed questionnaire. The data generated and analyzed included age and gestation weeks, parity, mode of intervention, associated organ dysfunctions, reasons for near-miss and critical intervention accompanied to manage the near-miss cases. Results were presented in mean ± SD and percentages, wherever applicable. Results: There were 4617 deliveries with 28 near-miss cases. The major factors contributing near-miss events were obstetric haemorrhage followed by hypertensive disorder. Three fourth (n=21) of cases required blood transfusion and almost all cases (n=26) required ICU management. Coagulation disorder was observed in majority of cases (n=23) followed by cardiovascular, respiratory and uterine atony. Conclusions: In this study, maternal near-miss event was mainly attributable to obstetric haemorrhage followed by hypertension and sepsis. Major organ-system disorders observed were coagulation disorder, cardiovascular, respiratory and uterine disorders. Almost all the cases were managed in ICU and majority of them required blood transfusion.